2018
DOI: 10.1002/jbio.201800102
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared laser photons induce glutamate release from cerebrocortical nerve terminals

Abstract: Although photons have been repeatedly shown to affect the functioning of the nervous system, their effects on neurotransmitter release have never been investigated. We exploited in vitro models that allow effects involving neuron-astrocyte network functioning to be detected (mouse cerebrocortical slices) and dissected these effects at cerebrocortical nerve endings and astrocyte processes. Infrared light proved able to induce glutamate release by stimulating glutamatergic nerve endings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Calcium may have also a role in this issue. Indeed, de Freitas Rodrigues [ 34 ] and Pigatto et al [ 110 ] showed that PBM decreased TRPV1 expression, and Amaroli et al [ 111 ] demonstrated that 808-nm laser light induced calcium-dependent glutamate release from nerve terminals, only in the presence of mitochondria. It is known that glutamate release is associated with ATP [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium may have also a role in this issue. Indeed, de Freitas Rodrigues [ 34 ] and Pigatto et al [ 110 ] showed that PBM decreased TRPV1 expression, and Amaroli et al [ 111 ] demonstrated that 808-nm laser light induced calcium-dependent glutamate release from nerve terminals, only in the presence of mitochondria. It is known that glutamate release is associated with ATP [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we previously showed the ability of 808 nm 1 W, 1 W/cm 2 and 60 J/cm 2 to modulate the calcium homeostasis affecting mitochondria bioenergy production [26,27], through the mitochondrial respiratory chain [23,25,55,56], cell metabolism [26,50], and inflammatory cell pathways [57], to promote cell proliferation [50,55,57], tissue regeneration [28,30,58], and release of neurotransmitters [59]. Lastly, the target of PBM therapy and the alteration of energy category genes in both moderate and severe BP could also explain why our PBM therapy was unsuccessful if performed more than 1 year after the onset of palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Gliosomes are a purified preparation of astrocyte processes containing vesicles loaded with gliotransmitter, competent for gliotransmitter secretion [ 9 , 19 ]. Synaptosomes are a purified preparation of nerve terminals, negligibly contaminated by astrocytic, microglial or oligodendroglial particles, competent for the release of neurotransmitters in response to different stimulations [ 20 , 24 , 25 ]. Gliosomes and synaptosomes were washed by centrifugation, and the pellets were resuspended in standard physiological medium buffered with HEPES or in loading buffer for the WB analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, we investigated the function of isolated cerebrocortical nerve terminals (synaptosomes) and astrocyte processes (gliosomes) prepared from adult Dach-SMOX mice. Isolated synaptosomes indeed preserve the features of in situ nerve terminals, and reflect the behaviour of the presynaptic terminals in neuron–astrocyte networks [ 18 , 19 , 20 ], while gliosomes preserve the features and reflect the behaviour of the astrocyte processes in the networks [ 19 , 21 , 22 ]. In synaptosomes and gliosomes from Dach-SMOX and control mice, we assessed the PA content, the oxidative stress markers, and the influx of calcium in response to glutamate receptor activation.…”
Section: Introductionmentioning
confidence: 99%